Impacts of Rural Road Development on Local Traffic: A Case Study of Tangail District - Rahman, Md Touhidur; Nur, S M Shihab (Journal of Bangladesh Institute of Planners, 2018)
Construction and maintenance of rural roads bring multiple socio-economic benefits to the people of rural areas as well as significant change in the movement of local traffic. The aim of this study is to assess the impacts of rural roads development of the pattern of local traffic. The study area of this research is Tangail, which is a district of Bangladesh. For completing the study, data were collected from whole Tangail district by doing questionnaire surveys and holding focus group discussions with shopkeepers and officials of Local Government Engineering Department (LGED), which is the responsible authority for construction and maintenance of rural roads. Besides, educational institutions were also surveyed and information regarding land use changes were collected. Before the development works, people were mainly dependent on nonmotorized transport modes and most of the roads were not usable throughout the year. After the development works, the non-motorized modes have declined and volume of motorized modes has increased significantly. At present, 87.3% shopkeepers are getting more customers than before and average reduction in freight cost is 35.42 BDT. The number of semi-paved and paved residential buildings has also increased. Students, who are a major part of the local traffic, their attendance in schools has increased dramatically as a result of road development. However, development of rural roads has also created some problems to the local people such as heavy traffic and increased number of accidents because of high speed of motorized vehicles. JBIP, Vol. 11, 2018 (Printed in June 2020), pp. 77-87